Formulation and Evaluation of Liquid Soap Incorporated with Salvia Rosmarinus (Rosemary) Extract and Lavandula (Lavender) Essential Oil for Antibacterial and Antioxidant Effects - Abdul Aziz, Nur Maisarah; Mohamed, Elizah (Progress in Engineering Application and Technology, 2025)
Skin sensitivity is a common concern, often worsened by harsh chemical products that disrupt the skin’s natural balance. This study explores the development of a polyherbal liquid soap formulated with rosemary (Salvia rosmarinus) extracts and lavender (Lavandula) essential oil, designed to offer a gentle yet effective cleansing solution for sensitive skin. The soap harnesses the natural properties of these botanicals to reduce inflammation, support the skin barrier, and promote overall skin health. Fresh rosemary was extracted using advanced Soxhlet and Ultrasound-Assisted Extraction (UAE) methods, while lavender essential oil was incorporated for its therapeutic benefits. The final liquid soap formulation had a pH of 9.47, a value typical for conventional soaps yet safe for sensitive skin. Stability tests conducted at 4 °C and 25 °C showed no signs of degradation, confirming its suitability for long-term use. The soap’s antioxidant activity was evaluated through the DPPH assay, demonstrating significant potential to counteract oxidative damage. Additionally, antibacterial properties assessed via the Disc Diffusion method revealed notable inhibitory effects against Staphylococcus epidermidis and Escherichia coli, showcasing its ability to combat harmful microorganisms. These findings suggest that this polyherbal liquid soap provides an effective, safe, and sustainable option for individuals with sensitive skin, blending natural ingredients with advanced extraction techniques to set a new standard for natural skincare products.